2023
DOI: 10.1101/2023.01.17.523179
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Transcriptomics of Fibrotic Lungs Unveils Aging-associated Alterations in Endothelial and Epithelial Cell Regeneration

Abstract: Lung regeneration deteriorates with aging leading to increased susceptibility to pathologic conditions, including fibrosis. Here, we investigated bleomycin-induced lung injury responses in young and aged mice at single-cell resolution to gain insights into the cellular and molecular contributions of aging to fibrosis. Analysis of 52,542 cells in young (8 weeks) and aged (72 weeks) mice identified 15 cellular clusters, many of which exhibited distinct injury responses that associated with age. We identified Pdg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 100 publications
2
5
0
Order By: Relevance
“…This study, in which most patients were of older age, also observed a loss of general capillary and aerocyte ECs in both age-related diseases compared to healthy control tissue, as well as an increase of venous EC populations. Similar observations were made in drug-induced IPF in mice, where the influence of age on disease outcome was observable by reduced aerocyte abundance, an increase of venous ECs, and remodeling of the vasculature in 18-month old mice, stressing the impact of ECs in this condition [ 77 ]. In fibrotic conditions (COVID-19, IPF), an enrichment of genes involved in cellular stress, as well as signatures suggestive of hampered immunoregulation and loss of vessel wall integrity were furthermore found [ 7 ].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…This study, in which most patients were of older age, also observed a loss of general capillary and aerocyte ECs in both age-related diseases compared to healthy control tissue, as well as an increase of venous EC populations. Similar observations were made in drug-induced IPF in mice, where the influence of age on disease outcome was observable by reduced aerocyte abundance, an increase of venous ECs, and remodeling of the vasculature in 18-month old mice, stressing the impact of ECs in this condition [ 77 ]. In fibrotic conditions (COVID-19, IPF), an enrichment of genes involved in cellular stress, as well as signatures suggestive of hampered immunoregulation and loss of vessel wall integrity were furthermore found [ 7 ].…”
Section: Introductionsupporting
confidence: 65%
“…From a human point-of-view, while extensive atlasing efforts [ 9 , 75 , 76 ] allowed for an all-encompassing overview of endothelial populations in healthy human lung tissue, a thorough interrogation of how aging affects these is still lacking. However, multiple studies analyzed age-related pulmonary diseases, such as IPF (idiopathic pulmonary fibrosis), COPD (chronic obstructive pulmonary disorder) and COVID-19 [ 7 , 66 , 77 , 78 ], and helped reveal EC phenotypes and gene expression signatures that may be at play in healthy aging as well. For instance, in human lung tissue from IPF, smokers, and COPD patients, a specialized systemic/peribronchial EC population was found, defined by the marker gene COL15A1 , which was enriched in IPF lungs around fibrotic areas [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…20 ADAMDEC1 is critical in the fibroblastic response to tissue remodeling and healing during colitis 21 and PDGFRA+ fibroblasts display a proliferative phenotype and are a major source of collagen. 22,23 Based on the prominent role of fibroblasts in CDs signaling, the differences largely restricted to the LP1/2 fraction, the over-representation of distinct fibroblast types, and the strong contribution to transcriptional changes in CDs, we sought a unifying molecule and identified CDH11 as the only cell surface receptor shared by the CXCL14+ and MMP/WNT5A+ fibroblasts. While also expressed in macrophages, CDH11 is primarily responsible for mediating homophilic stromal cell-cell interactions, [24][25][26][27] is upregulated in fibrotic disorders of the lung, 24 liver, 25 skin, 26 intestine, 27 and its inhibition attenuates fibrosis in multiple animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells were detected in multiple organs fibrosis and adhesion tissues, although their function is unknown. For example, RGCC was linked to renal fibrosis, while ACKR1 + ECs promoted pulmonary fibrosis 61,62 . Besides, the similar profibrotic phenomenon of ACKR1 + ECs was also found in hepatic fibrosis 6 .…”
Section: Discussionmentioning
confidence: 99%